On the existence of integrable solutions to nonlinear elliptic systems and variational problems with linear growth - Beck, L; Bulíček, M; Málek, J; Süli, E (Springer Berlin Heidelberg, 2017)
We investigate the properties of certain elliptic systems leading, a priori, to solutions that belong to the space of Radon measures. We show that if the problem is equipped with a so-called asymptotic radial structure, then the solution can in fact be understood as a standard weak solution, with one proviso: analogously to the case of minimal surface equations, the attainment of the boundary value is penalized by a measure supported on (a subset of) the boundary, which, for the class of problems under consideration here, is the part of the boundary where a Neumann boundary condition is imposed.